Hybrid didactic design in mathematics learning on fraction: A hermeneutic phenomenology - Ahmad Muzaki; Ita Chairun Nissa; Sri Yuliyanti; Masjudin; Muhamad Galang Isnawan (Jurnal Elemen, 2025)
Although many studies have involved fractions in the elementary school curriculum, research on this topic at the junior high school level has been limited, particularly in identifying the factors causing student learning difficulties and designing alternative didactic approaches to overcome these challenges. Therefore, this study aimed to investigate these aspects. Hermeneutic phenomenology was used in this study. The participants in this research were students from a junior high school in Lombok, Indonesia, consisting of 29 eighth-grade students (aged 14-18), most of whom were female and from the Sasak ethnic group. Instrument, such as fraction operation tests, in-depth interview guidelines, and a hybrid didactic design for mathematics learning. Data related to learning difficulties were analyzed using a thematic analysis approach with NVivo-12 software. The study's findings revealed that students' low ability to operate integers, especially multiplication and division, was a primary factor in learning difficulty. The hybrid mathematics learning design sequence consists of three stages. The first stage encompasses several activities, namely Let’s Guess and Let’s Read. The second stage involved activities like Let’s Search, Let’s Discuss, and Let’s Conclude. The third stage comprised activities of Let’s Practice and Self-Reflection.